Edukasi Pajak Berbasis Kearifan Lokal Menuju SDGs 4 Berkualitas - Rochma Sudiati; Surya Anugrah; Benyamin Suwondo; Virgiawan Virgiawan (Jurnal Bersama Pengabdian Kepada Masyarakat (SAMAMAS), 2025)
This community service program aims to improve vocational school students' understanding of taxation through education based on local wisdom integrated with digital literacy. This activity was carried out at SMK Negeri 11 Bekasi using an interactive training approach and digital taxation simulations such as e-Filing and e-Billing. The program also integrates local values such as mutual cooperation, social justice, and collective responsibility to provide a relevant social context regarding the importance of taxes. The evaluation results obtained from this activity show a significant positive impact on students' understanding. The role and support of SMK Negeri 11 Bekasi facilitated the smooth running of this activity. Additionally, there has been a positive change in students' attitudes and interest in the world of taxation, including career interest in this field. This approach supports the achievement of SDG 4 (quality education) through partnerships between universities, schools, and the community, and plays a role in creating a young generation that is tax-aware and digitally literate.